Determination of diffusion length from within a confined region with the use of EBIC - Ong, Vincent K. S. (2009)
A new method of extracting minority carrier diffusion length from within a confined region of material is presented in this paper. This technique uses the finite difference method and can be used on samples where the diffusion lengths are longer than the width of the region. This cannot be achieved using the conventional method, which evaluates the negative reciprocal of the slope of the EBIC signals line scan plotted on a semi-logarithmic scale. A limitation of this method is that the beam entrance surface of the sample is assumed to have negligible surface recombination.